Agriculture Purba-Based Productive Waqf Model as A Circular Economic Aplication: A Qualitative Study at Yayasan Al-Bahjah - Muhamad Saechu; Abdul Aziz; Wartoyo; Sri Rokhlina Sari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the concept of Ancient Agriculture developed by Deden Lesmana and its integration with productive waqf development as an innovative approach to sustainable community empowerment. Using a qualitative research approach, this study explores how ecological agriculture, circular economy principles, and Islamic social finance can be integrated to support sustainable development and enhance the utilization of waqf assets. Data were collected through literature reviews, document analysis, and conceptual exploration of productive waqf management practices. The findings indicate that Ancient Agriculture provides an effective and sustainable model for transforming idle waqf land into productive assets through low-cost, environmentally friendly agricultural practices. The model emphasizes the use of locally available resources, organic waste recycling, natural fertilizers, and community participation, thereby reducing dependency on external inputs and promoting environmental conservation. Furthermore, the integration of Ancient Agriculture with productive waqf creates opportunities for generating continuous economic benefits while preserving the principal value of waqf assets in accordance with Islamic principles. The study also reveals that this model contributes significantly to economic empowerment by creating employment opportunities, strengthening local food security, and increasing community income. From an environmental perspective, Ancient Agriculture supports biodiversity conservation, soil fertility improvement, waste reduction, and sustainable resource management through the implementation of circular economy practices. In addition, the model aligns with several Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty), Goal 2 (Zero Hunger), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action). The study concludes that the integration of Ancient Agriculture and productive waqf offers a promising framework for sustainable development, community resilience, and Islamic social finance innovation. It is recommended that waqf institutions, policymakers, and local communities collaborate to expand the implementation of this model in various regions.